2019
DOI: 10.1101/580746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial endosymbionts influence fungal transcriptional profiles with implications for host response in the human fungal pathogensRhizopus microsporusandRhizopus delemar

Abstract: Mucorales spores, the causative agents of mucormycosis, interact with the innate immune system to cause acute, chronic, or resolving infection. Understanding the factors that influence disease initiation and progression is key to understanding mucormycosis and developing new treatments. Complicating this, mucormycosis can be caused by a number of species that span the Mucorales genus and may be host to bacterial endosymbionts. This study sets out to examine the differences between two species in the Mucorales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Loss of the endosymbiont had profound impacts on R. microsporus response to phagocytosis, leading to altered regulation of 359 genes, including inappropriate repression of genes involved in siderophore activity and iron scavenging. 72 We observed a similar global change in the intensity of the fungal response to phagocytosis in a cured isolate of R. delemar lacking an unculturable endosymbiont with high 16S sequence homology to other unculturable bacteria (Accession number MK573034). 72 Together, our findings support a mutualistic lifestyle for R. pickettii and R. microsporus .…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Loss of the endosymbiont had profound impacts on R. microsporus response to phagocytosis, leading to altered regulation of 359 genes, including inappropriate repression of genes involved in siderophore activity and iron scavenging. 72 We observed a similar global change in the intensity of the fungal response to phagocytosis in a cured isolate of R. delemar lacking an unculturable endosymbiont with high 16S sequence homology to other unculturable bacteria (Accession number MK573034). 72 Together, our findings support a mutualistic lifestyle for R. pickettii and R. microsporus .…”
Section: Resultssupporting
confidence: 56%
“…72 We observed a similar global change in the intensity of the fungal response to phagocytosis in a cured isolate of R. delemar lacking an unculturable endosymbiont with high 16S sequence homology to other unculturable bacteria (Accession number MK573034). 72 Together, our findings support a mutualistic lifestyle for R. pickettii and R. microsporus .…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Specifically, Ralstonia pickettii promotes the ability of R. microsporus to survive killing by macrophages ( Itabanga et al, 2019 ). In a transcriptome-focused companion paper, Sephton-Clark et al (2019) examined the transcriptional response of J774.1 macrophages following phagocytosis of R. delemar and R. microsporus either with or without their bacterial endosymbionts living inside them. This study revealed that endosymbiont-cured R. microsporus elicited a much stronger pro-inflammatory response than did R. microsporus which contained the bacterial endosymbiont, consistent with increased ability of macrophages to kill R. pickettii -cured R. microsporus .…”
Section: Future Directionsmentioning
confidence: 99%